Research Paper: Cross State-dependent Learning Interaction Between Scopolamine and Morphine in Mice: The Role of Dorsal Hippocampus - Morteza Maleki; Majid Hassanpour-Ezatti; Majid Navaeian (Basic and Clinical Neuroscience, 2017)
Introduction: The current study aimed at investigating the existence of the cross state-dependent learning between morphine and scopolamine (SCO) in mice by passive avoidance method, pointing to the role of CA1 area.  Methods: The effects of pre-training SCO (0.75, 1.5, and 3 μg, Intra-CA1), or morphine (1, 3, and 6 mg/kg, intraperitoneal (i.p.) was evaluated on the retrieval of passive avoidance learning using step-down task in mice (n=10). Then, the effect of pretest administration of morphine (1.5, 3, and 6 mg/kg, i.p.) was examined on passive avoidance retrieval impairment induced by pre-training SCO (3 μg/mice, Intra-CA1). Next, the effect of pretest Intra-CA1 injection of scopolamine (0.75, 1.5, and 3 μg/mice) was evaluated on morphine (6 mg/kg, i.p.) pre-training deficits in this task in mice. Results: The pre-training Intra-CA1 injection of scopolamine (1.5 and 3 μg/mouse), or morphine (3 and 6 mg/kg, i.p.) impaired the avoidance memory retrieval when it was tested 24 hours later. Pretest injection of both drugs improved its pre-training  impairing effects on mice memory. Moreover, the amnesia induced by the pre-training injections of scopolamine (3 μg/mice) was restored significantly (P<0.01) by pretest injections of morphine (3 and 6 mg/kg, i.p.). Similarly, pretest injection of scopolamine (3 μg/mice) restored amnesia induced by the pre-training injections of morphine (6 mg/kg, i.p.), significantly (P<0.01).  Conclusion: The current study findings indicated a cross state-dependent learning between SCO and morphine at CA1 level. Therefore, it seems that muscarinic and opioid receptors may act reciprocally on modulation of passive avoidance memory retrieval, at the level of dorsal hippocampus, in mice.